Structure-Based Design and Molecular Simulations of Some Quercetin-Based Drugs as Repurposable Inhibitors of SARS-CoV-2 Main Protease - Ayipo, Yusuf Oloruntoyin; Alananzeh, Waleed A; Abdulsalam, Zuliah Abiola; Badeggi, Umar Muhammad; Jimoh, Akeem Adebayo; Osunniran, Wahab Adesina; Mordi, Mohd Nizam (Trends in Sciences, 2022)
In this study, virtual screening and molecular dynamics (MD) protocols were applied to screen 2826 FDA-approved natural product drugs from the Selleckchem.com library for prospective inhibitors of the SARS-CoV-2 main protease. From the virtual screening through HTVS, SP and XP docking analysis, hyperoside, rutin hydrate, rutoside and quercitrin displayed a stronger binding affinity with respective XP docking scores of –11.389, –11.340, –11.087 and –10.232 kcal/mol than co-crystallized N-[2-(5-fluoro-1H-indol-3-yl)ethyl]acetamide (HWH) and positive inhibitors, lopinavir and ritonavir which scored –5.493, –6.463 and –6.221 kcal/mol respectively. Selectively, the binding free energy, MMGB(SA) of hyperoside and rutin hydrate was observed as –21.55 and –25.82 kcal/mol respectively compared to lopinavir and ritonavir with –17.66 and –5.28 kcal/mol respectively. Consistently, the selected drugs displayed good thermodynamics conformational stability, thus, recommended as promising repurposable inhibitors of the SARS-CoV-2 main protease amenable for further studies. HIGHLIGHTS Main protease of the SARS-CoV-2 represents a plausible target for mitigating viral replication Natural repurposable drugs are safer and cheaper for combating COVID-19 Hyperoside, rutin hydrate and quercitrin displayed strong binding and stability with the viral main protease They are recommended as repurposable inhibitors of SARS-CoV-2 main protease for further studies GRAPHICAL ABSTRACT